1987
DOI: 10.1002/ccd.1810130410
|View full text |Cite
|
Sign up to set email alerts
|

Optimal ECG monitoring during percutaneous transluminal coronary angioplasty of the left anterior descending artery

Abstract: During percutaneous transluminal coronary angioplasty (PTCA) frontal ECG leads are routinely monitored. The detection of ST segment deviation during the procedure is important for decisions regarding guiding catheter seating and the timing of balloon inflation and deflation. ST segment deviation appears on intracoronary electrograms in the absence of changes on the surface ECG in many patients, while the reverse is true in some individuals. When a precordial lead is employed, V5 or V6 is most commonly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Most of these patients have ischemia observed through monitoring with a single lead (V2; 79%). This observation is similar to results obtained by Feldman et al [7], who noted ST deviation in 11 of 14 patients (79%). These investigators did not monitor lead V 1 , V3, or V4.…”
Section: Discussionsupporting
confidence: 92%
“…Most of these patients have ischemia observed through monitoring with a single lead (V2; 79%). This observation is similar to results obtained by Feldman et al [7], who noted ST deviation in 11 of 14 patients (79%). These investigators did not monitor lead V 1 , V3, or V4.…”
Section: Discussionsupporting
confidence: 92%
“…Application of the Intracoronary Electrocardiogram to Study Regional Ischemia Using the IC‐ECG to evaluate the S‐ECG, it was found that lead V 2 was the single best lead to detect LAD ischemia, 60 and that left circumflex distribution transmural ischemia was not well reflected by S‐ECG 61 . Using the IC‐ECG and collateral flow index measured during vascular occlusion in angiographically normal arteries, Wustmann et al showed that functional collaterals exist and could prevent ischemia in 20–25% of subjects 62 .…”
mentioning
confidence: 99%